Testicular involution prior to sex change in gilthead seabream is characterized by a decrease in DMRT1 gene expression and by massive leukocyte infiltration - Meseguer José; Mulero Victoriano; García-Alcazar Alicia; Chaves-Pozo Elena; Liarte Sergio; García-Ayala Alfonsa (BMC, 2007)
Abstract Background Leukocytes are found within the testis of most, if not all, mammals and are involved in immunological surveillance, physiological regulation and tissue remodelling. The testis of seasonal breeding fish undergoes a regression process. In the present study, the second reproductive cycle (RC) of the protandrous seasonal teleost fish, gilthead seabream, was investigated and the presence of leukocytes analysed. Special attention has been paid to the testicular degenerative process which is particularly active in the last stage of the second RC probably due to the immediacy of the sex change process. Methods Sexually mature specimens (n = 10-18 fish/month) were sampled during the second RC. Some specimens were intraperitoneally injected with bromodeoxyuridin (BrdU) before sampling. Light and electron microscopy was used to determine the different stages of gonadal development and the presence of leukocytes and PCR was used to analyse the gene expression of a testis-differentiating gene and of specific markers for macrophages and B and T lymphocytes. Immunocytochemistry and flow cytometry were performed using a specific antibody against acidophilic granulocytes from the gilthead seabream. Cell proliferation was detected by immunocytochemistry using an anti-BrdU antibody and apoptotic cells by in situ detection of DNA fragmentation. Results The fish in the western Mediterranean area developed as males during the first two RCs. The testis of all the specimens during the second RC underwent a degenerative process, which started at post-spawning and was enhanced during the testicular involution stage, when vitellogenic oocytes appeared in the ovary accompanied by a progressive increase in the ovarian index. However, only 40% of specimens were females in the third RC. Leukocytes (acidophilic granulocytes, macrophages and lymphocytes) were present in the gonad and acidophilic granulocyte infiltration occurred during the last two stages. At the same time DMRT1 gene expression decreased. Conclusions The results demonstrate that innate and adaptive immune cells are present in the gonads of gilthead seabream. Moreover, the whole fish population underwent a testicular degenerative process prior to sex change, characterized by high rates of apoptosis and necrosis and accompanied by an infiltration of acidophilic granulocytes and a decrease in DMRT1 levels.